Central nervous system pathology progresses independently of KC and CXCR2 in globoid-cell leukodystrophy. - Adarsh S Reddy (Public Library of Science (PLoS), 2014)
Globoid-cell Leukodystrophy (GLD; Krabbe's disease) is a rapidly progressing inherited demyelinating disease caused by a deficiency of the lysosomal enzyme Galactosylceramidase (GALC). Deficiency of GALC leads to altered catabolism of galactosylceramide and the cytotoxic lipid, galactosylsphingosine (psychosine). This leads to a rapidly progressive fatal disease with spasticity, cognitive disability and seizures. The murine model of GLD (Twitcher; GALC-/-) lacks the same enzyme and has similar clinical features. The deficiency of GALC leads to oligodendrocyte death, profound neuroinflammation, and the influx of activated macrophages into the CNS. We showed previously that keratinocyte chemoattractant factor (KC) is highly elevated in the CNS of untreated Twitcher mice and significantly decreases after receiving a relatively effective therapy (bone marrow transplantation combined with gene therapy). The action of KC is mediated through the CXCR2 receptor and is a potent chemoattractant for macrophages and microglia. KC is also involved in oligodendrocyte migration and proliferation. Based on the commonalities between the disease presentation and the functions of KC, we hypothesized that KC and/or CXCR2 contribute to the pathogenesis of GLD. Interestingly, the course of the disease is not significantly altered in KC- or CXCR2-deficient Twitcher mice. There is also no alteration in inflammation or demyelination patterns in these mice. Furthermore, transplantation of CXCR2-deficient bone marrow does not alter the progression of the disease as it does in other models of demyelination. This study highlights the role of multiple redundant cytokines and growth factors in the pathogenesis of GLD.